30 Acute Unprotected Left Mainstem Occlusion Emergency Percutaneous Coronary Intervention: Analysis of the British Cardiovascular Intervention Society Database. (31st May 2014) - Patel, Niket; Bennett, Derrick; Rahimi, Kazem; Kassmis, George; Ludman, Peter; Banning, Adrian
Abstract : Introduction: Limited data exists about management and outcome following presentation with unprotected left mainstem occlusion (ULMSO). To evaluate in-hospital outcomes and one-year mortality of patients presenting with ULMSO treated with primary percutaneous coronary intervention (PPCI). Methods: 400, 985 PCI cases were recorded in the British Cardiovascular Intervention Society database of all PCI cases in the UK from January 2007 to August 2012. 1, 473 patients underwent emergency unprotected left mainstem (LMS) PPCI (1.6% of all PPCI). 389 patients having emergency PPCI (0.44% of all PPCI) presented with ULMSO (occlusive disease defined as TIMI flow 0/1 and stenosis >75%). These ULMSO patients were compared with 733 emergency patients treated with non-occlusive LMS disease. All-cause mortality was tracked by the office of national statistics and life status was available at 7, 30, 90 and 365 days following intervention. Results: 86, 672 patients had PPCI within the observation period (5.7% 30-mortality). The approximate incidence of ULMSO PPCI is 11 cases/year/100, 000 population. Presentation with ULMSO was associated with a doubling in the likelihood of peri-procedural shock (60% vs. 29%; p < 0.001) and/or IABP support (56% vs. 29%; p < 0.001) compared to those with non-occlusive LMS disease. In-hospital (40% vs. 18%; p < 0.001), and 1-year mortality (54% vs. 32%; p < 0.001) was higher in patients with ULMSO compared with patients presenting with a patent LMS. 1-year mortality in the ULMSO groups was 2.5-fold higher in those with peri-procedural cardiogenic shock (CS; 72% vs. 29%; p < 0.001). However, late mortality rates were independent of initial haemodynamic status (30-day vs. 1-year mortality was 58% vs. 72% respectively in the ULMSO group with CS and 21% vs. 29% respectively in those without CS) (Figure 1 ). Conclusions: In patients undergoing PPCI for ULMSO, acute outcomes are poor and additional therapies are required to improve outcome. However long-term outcomes for survivors of ULMSO are encouraging.